Proliferation-apoptosis balance in Staphylococcus aureus chronically infected bovine mammary glands during involution - Andreotti, Carolina Soledad; Pereyra, Elizabet Amanda Lorena; Sacco, Sofía Clara; Baravalle, Celina; Renna, Maria Sol; Ortega, Hugo Hector; Calvinho, Luis Fernando; Dallard, Bibiana Elisabet (2018)
The objective of this study was to determine whether Staphylococcus aureus chronic intramammary infection (IMI) influences expression of proteins related to regulation of proliferation and apoptosis processes and proliferation/apoptosis index during active involution in bovine mammary gland. Twenty-one Holstein non-pregnant cows in late lactation either uninfected or with chronic naturally acquired S. aureus IMI were included in this study. Cows were slaughtered at 7, 14 and 21 d after cessation of milking and samples for immunohistochemical analysis were taken. Protein expression of Bcl-2, Bax, Fas and active caspase-3 in mammary tissue was significantly affected by chronic S. aureus IMI, all showing increased immunoexpression in S. aureus-infected quarters at all involution stages. The percentage of apoptotic cells was increased by IMI in both mammary parenchyma and stroma, and the percentage of parenchymal and stromal cell proliferation was also increased. The proliferation/apoptosis ratio was significantly increased by IMI only in stromal cells. This imbalance to favour proliferation in S. aureus-infected mammary quarters could be one of the underlying causes that induce aberrant involution with permanence of nonsecretory tissue and increase of stromal components.